Students' Perception of Online Learning During Covid-19: An Evidence from University of Muhammadiyah Banda Aceh, Indonesia - Safura, Siti (Universitas Terbuka, 2021)
The pandemic of Coronavirus has influenced all levels of education in the whole world. This impact forces the Ministry of Education to switch from traditional education to online education. As a result, educators must run this policy to teach the classroom and students must adapt to this situation. This research aimed to find out students' perception of online learning during the Coronavirus pandemic. This research employed the qualitative design and used the survey method to distribute the questionnaires. The object of this research was twenty-seven students of the English Department, University of Muhammadiyah Aceh. The obtained data was analyzed through descriptive analysis to see how online class is perceived by students during the pandemic. The result of this research shows that the students share the positive perceptions toward online learning during the Coronavirus pandemic. The finding also displays the hesitation of students in deciding the problem faced in having the online class.